2022
DOI: 10.3758/s13414-022-02557-5
|View full text |Cite
|
Sign up to set email alerts
|

Pupillometry signatures of sustained attention and working memory

Abstract: There exists an intricate relationship between attention and working memory. Recent work has further established that attention and working memory fluctuate synchronously, by tightly interleaving sustained attention and working memory tasks. This work has raised many open questions about physiological signatures underlying these behavioral fluctuations. Across two experiments, we explore pupil dynamics using real-time triggering in conjunction with an interleaved sustained attention and working memory task. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The pupil does not only respond to changes in visual input but also to internal factors such as cognitive activity. Pupil-size changes have been observed in a variety of tasks and contexts, such as problem solving, working memory, decision making, and attention (Alnæs et al, 2014; Hess & Polt, 1960, 1964; Kahneman & Beatty, 1966; Keene et al, 2022). In general, increases in task difficulty or processing load lead to pupil dilation irrespective of the specific cognitive processes involved, and larger pupils are often associated with better performance (for reviews see Beatty, 1982; Laeng et al, 2012; Loewenfeld, 1958; Mathôt, 2018; Vilotijević & Mathôt, 2023).…”
mentioning
confidence: 99%
“…The pupil does not only respond to changes in visual input but also to internal factors such as cognitive activity. Pupil-size changes have been observed in a variety of tasks and contexts, such as problem solving, working memory, decision making, and attention (Alnæs et al, 2014; Hess & Polt, 1960, 1964; Kahneman & Beatty, 1966; Keene et al, 2022). In general, increases in task difficulty or processing load lead to pupil dilation irrespective of the specific cognitive processes involved, and larger pupils are often associated with better performance (for reviews see Beatty, 1982; Laeng et al, 2012; Loewenfeld, 1958; Mathôt, 2018; Vilotijević & Mathôt, 2023).…”
mentioning
confidence: 99%
“…Research has shown that working memory load can influence speech perception, suggesting an asymmetric impact on both low-level auditory encoding and high-level language processing of speech, likely due to attention redistribution under mnemonic load ( 36 ). Another study confirmed that attention and working memory exhibit synchronous fluctuations, demonstrated through interconnected continuous attention and working memory tasks ( 37 ). Notably, our study found that moderate-intensity aerobic exercise could enhance the working memory of persons with stroke with mild cognitive impairment (MCI).…”
Section: Discussionmentioning
confidence: 74%
“…Much of the early research exploring the role of alertness on memory defined alertness as needing sleep or not (Aguirre et al, 1985;Gorissen et al, 1997;Rogers & Rosenberg, 1990). However, contemporary research has expanded our understanding of alertness to include momentary fluctuations that influence both attentional control and memory processes (deBettencourt et al, 2018(deBettencourt et al, , 2019Keene et al, 2022). We also better understand the neuroanatomical structures responsible for modulating alertness (Ross & Van Bockstaele, 2021;Van Egroo et al, 2022).…”
Section: Alertness and Procedural Memorymentioning
confidence: 99%